Інноваційна технологія виготовлення виливка лопаті робочого колеса радіально-осьової гідротурбіни - Бондаренко, В. С.; Безвесільна, О. М.; Пономаренко, Ольга; Бударін, О. С.; Марченко, Андрій; Акімов, Олег; Артьомова, Світлана; Михайлюков, В. П.; Євтушенко, С. Д. (Physico-technological Institute of Metals and Alloys, 2023)
The purpose of the study is to develop a progressive technology for casting the impeller blade of the Dniester Pumped Storage Power Station (PSPS). To solve the problem of improving the quality of castings, computer-integrated methods for modeling casting processes were used. The use of CAD/CAE programs has significantly reduced the time for the development of technological processes, created conditions for directional solidification of castings, calculated the optimal amount of head of castings and, by predicting the appearance of defect locations, reduced the shortage of castings. The production of a one-piece cast impeller blade made of SA-6NM stainless steel became possible after the reconstruction of the metallurgical production of Ukrenergymachines JSC and the overhaul of the electric arc furnace. Structural stability, stability of physical and mechanical properties in the production of CA-6NM steel is achieved by obtaining a given ratio of chromium and nickel equivalent using computer control of the steel composition during smelting. Stainless steel was smelted in two electric arc furnaces with basic lining. After release, the metal was sold through slotted lances in ladles with argon. The shaping equipment was represented by a complex volumetric model set. Spatial templates, core boxes and a model sign were made. In the manufacture of rods, frameworks of complex design and cold-hardening molding mixtures on chromite sands by the furan process were used. In the manufacture of rods for parts of heads of castings, exothermic materials were used. The reduction in the cost of blade castings from the transfer from a welded-cast version to a solid-cast one and the organization of their production in the conditions of the foundry shop of Ukrenergymachines JSC amounted to 30 %.